Urbanisation and rural development in developing countries: A review of pathways and impacts - Tekalign Gutu Sakketa (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
This paper reviews the current state of literature on the impacts of urbanization on rural development in developing countries, with an emphasis on Sub-Saharan Africa (SSA). It also provides a conceptual framework for linking these phenomena, and identifies research gaps that have important policy implications. In particular, this study identifies the following pathways through which urbanization can impact rural (economic) development: Production and consumption linkages, labor/employment linkages, financial linkages, land market linkages, linkages with information or public services, linkages with social interaction, and linkages with environmental externalities such as waste/pollution, environmental degradation and loss of biodiversity. To this end, the review has identified the following research gaps. First, although effective rural-urban planning, monitoring and evaluation of rural-urban development policies require better data, there is lack of data collection systems or their quality is poor. In this respect, investing in emerging data sources such as satellites data can help countries improve their data collection systems and measures. Second, research is needed to revise and reformulate better theoretical frameworks that take into account the uniqueness of African urban cities. Third, empirical evidence which documents to what extent and how rural-urban linkages provide an important arena for improving social interactions among neighbors, societies, and communities is needed. Finally, as many African countries continue to experience rapid urbanization (mostly urban sprawl), a thorough study of the impacts of urban externalities on agricultural productivity, food security, biodiversity, and the health of rural communities is necessary.
Keywords: D6; O1; Q1; R2; 330; Rural development; urbanization; rural-urban linkages; social cohesion; Sub-Saharan Africa; rapid review